Inspiratory muscle training enhances recovery post-COVID-19: a randomised controlled trial. Issue 4 (6th October 2022) - McNarry, Melitta A.; Berg, Ronan M.G.; Shelley, James; Hudson, Joanne; Saynor, Zoe L.; Duckers, Jamie; Lewis, Keir; Davies, Gwyneth A.; Mackintosh, Kelly A.
Background: Many people recovering from coronavirus disease 2019 (COVID-19) experience prolonged symptoms, particularly breathlessness. We urgently need to identify safe and effective COVID-19 rehabilitative strategies. The aim of the current study was to investigate the potential rehabilitative role of inspiratory muscle training (IMT). Methods: 281 adults (age 46.6±12.2 years; 88% female) recovering from self-reported COVID-19 (9.0±4.2 months post-acute infection) were randomised 4:1 to an 8-week IMT or a "usual care" waitlist control arm. Health-related quality-of-life and breathlessness questionnaires (King's Brief Interstitial Lung Disease (K-BILD) and Transition Dyspnoea Index (TDI)), respiratory muscle strength, and fitness (Chester Step Test) were assessed pre- and post-intervention. The primary end-point was K-BILD total score, with the K-BILD domains and TDI being key secondary outcomes. Results: According to intention to treat, there was no difference between groups in K-BILD total score post-intervention (control: 59.5±12.4; IMT: 58.2±12.3; p<0.05) but IMT elicited clinically meaningful improvements in the K-BILD domains for breathlessness (control: 59.8±12.6; IMT: 62.2±16.2; p<0.05) and chest symptoms (control: 59.2±18.7; IMT: 64.5±18.2; p<0.05), along with clinically meaningful improvements in breathlessness according to TDI (control: 0.9±1.7 versus 2.0±2.0; p<0.05). IMT also improved respiratory muscle strength and estimated aerobic fitness. Conclusions: IMT may represent an important home-based rehabilitation strategy for wider implementation as part of COVID-19 rehabilitative strategies. Given the diverse nature of long COVID, further research is warranted on the individual responses to rehabilitation; the withdrawal rate herein highlights that no one strategy is likely to be appropriate for all. IMT can significantly improve breathlessness and respiratory muscle function in people with long COVID, and represents an effective, home-based rehabilitation strategy that could be widely implemented as part of COVID-19 recovery strategies https://bit.ly/3HiEyz0